Application of the Method of Dimensionality Reduction to Simulate the Fretting Wear of Anisotropic Indenter; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Dmitriev A. I. Andrey Ivanovich (2015, 2015)
Title screen